2018
DOI: 10.1177/2379298118787798
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Operational Complexities: A Hands-On Experiential Exercise With Laundry

Abstract: Responding to change is a critical workforce competency and an essential skill for effective leadership and management along with abilities to work in a group, problem solve, and demonstrate critical thinking capabilities. In this experiential exercise, students collaborate in groups, think critically, and respond to customer demands in a fast-paced, competitive, and complex environment while trying to execute process tasks associated with running a laundry facility. Students search and retrieve products (shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Finally, research has shown that “the ability to work in group-based environments and across functional boundaries is a requirement of management” (Criscione-Naylor, 2020, p. 6). Through this exercise, students are introduced to the role of product managers while fine-tuning teamwork and creative thinking.…”
Section: Conceptual Groundingmentioning
confidence: 99%
“…Finally, research has shown that “the ability to work in group-based environments and across functional boundaries is a requirement of management” (Criscione-Naylor, 2020, p. 6). Through this exercise, students are introduced to the role of product managers while fine-tuning teamwork and creative thinking.…”
Section: Conceptual Groundingmentioning
confidence: 99%
“…We note that several other class exercises focus on the topic of leading change. For example, Criscione-Naylor (2020) introduced an exercise about leading change from an operational lens, while Virajanand (2020) developed a multimedia exercise that helps to determine change recipient’s readiness for change. In another exercise, Trefalt (2020) introduced a semester-long project that challenges students to engage in personal transformation.…”
mentioning
confidence: 99%